Middle East respiratory syndrome - Arabi, Yaseen M.; Balkhy, Hanan H.; Hayden, Frederick G.; Bouchama, Abderrezak; Luke, Thomas; Baillie, J. Kenneth; Al-Omari, Awad; Hajeer, Ali H.; Senga, Mikiko; Denison, Mark R.; Nguyen-Van-Tam, Jonathan S.; Shindo, Nahoko; et al. (Massachusetts Medical Society, 2017)
The Middle East respiratory syndrome is caused by a coronavirus that was first identified in Saudi Arabia in 2012. Periodic outbreaks continue to occur in the Middle East and elsewhere. This report provides the latest information on MERS.